2006
DOI: 10.1038/sj.bjc.6603284
|View full text |Cite
|
Sign up to set email alerts
|

Role of MEK/ERK pathway in the MAD2-mediated cisplatin sensitivity in testicular germ cell tumour cells

Abstract: Testicular germ cell tumour (TGCT) is the most common malignancy in young males. Although most TGCTs are sensitive to cisplatin-based chemotherapy, significant numbers of TGCT patients still relapse and die each year because of the development of resistance to cisplatin. Previously, we first reported that a key regulator of the mitotic checkpoint, mitotic arrest deficient-2 (MAD2), was a mediator of cisplatin sensitivity in human cancer cells. In this study, we investigated whether MAD2 played a role in cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 38 publications
3
22
1
Order By: Relevance
“…The overexpression of MAD2 has also been observed in a number of types of human cancer (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and appears to correlate with a variety of clinicopathological characteristics, such as metastasis and prognosis (13)(14)(15)(16)(17)(18)(19). Reduced expression of MAD2 has also been reported in certain human cancers (4,21) and is associated with resistance to chemotherapy using microtubuletargeting agents or DNA-damaging agents (22,23).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The overexpression of MAD2 has also been observed in a number of types of human cancer (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and appears to correlate with a variety of clinicopathological characteristics, such as metastasis and prognosis (13)(14)(15)(16)(17)(18)(19). Reduced expression of MAD2 has also been reported in certain human cancers (4,21) and is associated with resistance to chemotherapy using microtubuletargeting agents or DNA-damaging agents (22,23).…”
Section: Discussionmentioning
confidence: 98%
“…Certain studies have suggested a correlation between the overexpression of MAD2 and a variety of clinicopathological characteristics, such as histological grade (differentiation), metastasis and prognosis (13)(14)(15)(16)(17)(18)(19). However, reduced expression of MAD2 occurs in certain types of human cancer (4,21) and is associated with in vitro resistance to chemotherapy using microtubule-targeting agents or DNA-damaging agents (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have reported the active role of ERK in mediating the cytotoxicity of cisplatin and carboplatin (29)(30)(31)(32)(33)(34), and these studies have provided the basis to probe ERK activation as a molecular event in mediating the cytotoxic effect of carboplatin delivered via FRT liposomes. Our results demonstrated significantly higher ERK activation by FRT carboplatin liposomes as compared to free form and NT liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the role of ERK activation in cisplatin-and carboplatin-induced apoptosis (29)(30)(31)(32)(33)(34). It is thus interesting to probe if ERK activation would be observed in KB cells upon exposure to FRT carboplatin liposomes, which in turn, mediated the cytotoxic effect of these liposomes.…”
Section: Enhanced Erk Activation By Frt Carboplatin Liposomes As An Amentioning
confidence: 99%
“…This subsequently leads to an accumulation of securin (PTTG1) and cyclin B, thereby prolonging progression of mitosis to anaphase. Recent research has shown expression of MAD2, a direct target of the E2F family, to be associated with increased sensitivity to DNA-damaging agents (Cheung et al, 2005;Du et al, 2006;Fung et al, 2006).…”
Section: Chromosome 17mentioning
confidence: 99%